Respuesta :
Answer: 6
Step-by-step explanation:
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
6-3*n-(-12)=0
Step 1 :
Pulling out like terms :
Pull out like factors :
18 - 3n = -3 • (n - 6)
Equation at the end of step 1 :
Step 2 :
Equations which are never true :
2.1 Solve : -3 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
2.2 Solve : n-6 = 0
Add 6 to both sides of the equation :
n = 6
One solution was found :
n = 6
Answer: n = 6
Step-by-step explanation:
6 - 3n = -12
Collect like terms
-3n = -12-6
-3n = -18
Divide both side by -3
-3n/-3 = -18/-3
n = 6